Graške disertacije s področja slovenske literarne zgodovine - Smolej, Tone (Jezik in slovstvo, 2020)
The paper surveys the doctoral dissertations in the field of Slovenian literary history that were written by PhD candidates of Slovenian origin at the Seminar for Slavic philology, Charles-Ferdinand university, between 1881 and 1915.
Keywords: doctoral dissertations; doktorske disertacije; Gradec; Graz; Slovenian literary history; Slovenian students; slovenska literarna zgodovina; slovenski študenti